Edward Charles Elliott, Educator - Burrin, Frank K. (Purdue University Press, 1970)
A study of the 50-year career of Edward Charles Elliott is a study of the development of American education. Elliott had experience as a high school and college teacher, school system superintendent, state college system chancellor, and president of a Big Ten university, all during a period of change in American attitudes toward public schooling and rapid growth in education institutions. As president of Purdue University from 1922 to 1945, Elliott steered the school through years of expansion in size, prestige, and service. Student enrollment, staff, course offerings, buildings, and campus acreage more than doubled; the total value of the physical plant increased more than five-fold, and the schools of pharmacy, home economics, and graduate study were opened under Elliott's leadership. This book shows not only how Elliott helped make Purdue University what it is today, but documents educational trends from 1900 to 1950 and includes a lengthy bibliography of Elliott's writings to assist the student of higher education.